No longer newsworthy : how the mainstream media abandoned the working class - Martin, Christopher R. (ILR Press, an imprint of Cornell University Press, 2019)
"An exploration of how workers in the U.S. have been invisible for decades because the mainstream news media lost sight of the American working class"--